Minocycline for the treatment of cutaneous silicone granulomas: A case report. (2nd January 2016) - Crocco, Elisete; Pascini, Mirella; Suzuki, Nathalie; Alves, Renata; Proença, Thais; Lellis, Rute
Abstract : Silicone oil injections are often used for soft tissue augmentation and local and general adverse effects occurring from a few months to 15 years after injection have been reported. Here, we present a case of delayed granuloma formation due to liquid injectable silicone with large extent of involvement, which precluded surgical removal. Our patient was successfully treated with minocycline, considering its anti-inflammatory, immunomodulating and antigranulomatous properties. This case presents minocycline monotherapy as a useful treatment option for the management of severe granuloma induced by silicone use when surgical excision is not possible.